Interventional Management of Trigeminal neuralgia - Dessy R Emril (Universitas Syiah Kuala, 2009)
Abstract. Trigeminal neuralgia (TN) is a painful neuropathic pain condition affecting the face. It bas a significant impact on the quality of life and physical function of patients. Evidence suggests that the likely etiology is vascular compression of the trigeminal nerve leading to focal demyelination and aberrant neural discharge. Secondary causes such as multiple sclerosis or brain tumors can also produce symptomatic TN. Treatment must be individualized to each patient. Carbamazepine remains the drug of choice in the first-line treatment f TN. Minimal! invasive intervention al pain therapies and surgery. are possible options when drug therapy fails. Younger patients may benefit from microvascular decompression. Elderly patients with poorsurgical risk may be more suitable for percutaneous trigeminal nerve rhizolysis. The technique of radiofrequency rhizolysis of the trigeminal nerve is described in detail in this review. (JKS2009;2:83-89) Keywords: imerventional treatment; minimally invasive; pain management; radiofrequencyrhizolysis;trigeminal neuralgia